2012
DOI: 10.1103/physrevb.85.165316
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of self-assembled compositional core-shell structures in InxGa1xN nanowires

Abstract: We report the simulation of compositional core-shell structure formation in epitaxial InGaN nanowires (NWs) and its dependence on kinetic growth mode and epitaxial relation to substrate, based on atomistic-strain-model Monte Carlo simulations. On a lattice mismatched substrate, the layer-by-layer growth results in self-assembled core-shell structures with the core rich in the unstrained component (relative to the substrate), while the faceted growth mode leads to the strained core component, and both are disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…Also, in this continuous fully faceted model, the behaviour of each facets is counted in average. Thus, influence of different growth modes, such as layer-by-layer and step flow mentioned in Niu et al (2012), on the facet morphology is beyond the discussion in this paper.…”
Section: Introductionmentioning
confidence: 95%
“…Also, in this continuous fully faceted model, the behaviour of each facets is counted in average. Thus, influence of different growth modes, such as layer-by-layer and step flow mentioned in Niu et al (2012), on the facet morphology is beyond the discussion in this paper.…”
Section: Introductionmentioning
confidence: 95%
“…Recently, much attention has been paid to ternary IIIA nitrides, including InGaN, InAlN, and AlGaN nanostructures, because their band gaps and lattice parameters can be engineered by tuning their compositions. To obtain high crystal quality, nanostructures are often grown at elevated temperatures. However, instead of forming single-phase ternary alloy NRs, a core–shell structure is found in these self-induced NRs. , , Presently, most studies addressing formation of self-induced NRs depart from stipulating models relying on a thermodynamical equilibrium viewpoint and phase separation due to the immiscibility of a ternary alloy, which, in general, are not capable of explaining the formation of nanostructures of such complexity and diversity. For instance, AlGaN is miscible throughout the entire compositional range while a core–shell structure is still observed in self-indued NRs …”
Section: Introductionmentioning
confidence: 99%
“…However, instead of forming single-phase ternary alloy NRs, a core–shell structure is found in these self-induced NRs. 7 , 11 13 , 18 20 Presently, most studies addressing formation of self-induced NRs depart from stipulating models relying on a thermodynamical equilibrium viewpoint and phase separation due to the immiscibility of a ternary alloy, which, in general, are not capable of explaining the formation of nanostructures of such complexity and diversity. For instance, AlGaN is miscible throughout the entire compositional range while a core–shell structure is still observed in self-indued NRs.…”
Section: Introductionmentioning
confidence: 99%
“…In general, it is assumed that the GaN shell is formed by the radial overgrowth of the NWs during the deposition of the GaN barriers. However, some works have suggested that the formation of a narrower island in the center of the NWs can be energetically more favorable, so that the GaN shell is formed by the filling of the remaining lateral free space during the subsequent deposition steps, without any necessary radial growth of the NWs. , Another scenario suggested in the literature to explain the formation of the GaN shell is the possible spontaneous formation of a core–shell structure during the growth of the QDs due to a strain-driven segregation of the constituent binary compounds. , Furthermore, despite control in both, the chemistry (indium content) and shape of the QDs are critical for appropriately tuning the optoelectronic properties of these structures; very often the stacked QDs within the same NW show systematic changes in their shape from one QD to the next, even though they were grown under nominally identical conditions. ,, This change has been reported also for other lattice mismatched material systems such as (Al,Ga)­N/GaN NWs or vertically self-aligned InAs quantum dots on GaAs planar substrates …”
mentioning
confidence: 99%
“…11,12 Another scenario suggested in the literature to explain the formation of the GaN shell is the possible spontaneous formation of a core−shell structure during the growth of the QDs due to a strain-driven segregation of the constituent binary compounds. 13,14 Furthermore, despite control in both, the chemistry (indium content) and shape of the QDs are critical for appropriately tuning the optoelectronic properties of these structures; very often the stacked QDs within the same NW show systematic changes in their shape from one QD to the next, even though they were grown under nominally identical conditions. 12,15,16 This change has been reported also for other lattice mismatched material systems such as (Al,Ga)N/GaN NWs 17 or vertically self-aligned InAs quantum dots on GaAs planar substrates.…”
mentioning
confidence: 99%